Preparation method of pitch-based carbon fiber heat conduction sample subjected to intermittent graphitization and sample
The preparation of asphalt-based carbon fiber thermal samples through winding, cutting and batch graphitization treatment, solved the problem that asphalt-based carbon fiber cannot maintain a straight state during thermal conductivity testing, and improved the sample preparation efficiency and reliability of test data.
Patent Information
- Application Number
- CN202411728884.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, intermittent graphitized asphalt-based carbon fibers cannot remain straight during thermal conductivity testing, which affects the test accuracy.
By wrapping different raw material fibers into initial samples, cutting, binding, graphite paper wrapping and PAN-based carbon fiber binding, then batch graphitization is performed, folded symmetrically along the central position and cut, and finally, polyimide tape is spirally wound and cut into small cylindrical samples.
It ensures that the asphalt-based carbon fiber remains smooth after graphitization, improves the preparation efficiency of thermally conductive samples, and realizes thermal conductivity testing of mixed fibers of different proportions, ensuring the reliability of test data.
Smart Images

Figure CN119510088A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fiber material performance testing, and in particular to a method for preparing an intermittently graphitized asphalt-based carbon fiber thermal conductive sample and the sample. Background Art
[0002] Asphalt-based carbon fiber has many excellent properties, including low density, high modulus and high thermal conductivity. It is resistant to high temperatures and fatigue under extreme conditions, has a negative thermal expansion coefficient in the axial direction and is anisotropic. The thermal conductivity of asphalt-based carbon fiber is a key parameter for measuring the quality of materials. The sample holder in a conventional laser thermal conductivity instrument (transient method) can be used to conveniently test the thermal diffusion coefficient of the fiber and ultimately calculate the thermal conductivity of the asphalt-based carbon fiber. However, for fiber samples, the sample preparation problem for thermal conductivity testing has always been a difficult problem, mainly because the fibers are thin and soft, and it is difficult to prepare them into bulk samples like other solid materials.
[0003] When conventional rolled graphite fibers are tested for thermal conductivity in the fiber direction, the sample preparation process generally has two key steps: one is fiber bundling, which is to bundle appropriate fiber samples into a bundle with a diameter equivalent to that of the sample holder; the other is fiber cutting, which is to cut the bundled fibers into a suitable length, that is, the thickness of the test sample.
[0004] At present, conventional fiber thermal conductivity sample preparation is to manually unwind the fiber to a certain amount, and then arrange it into bundles according to the fiber direction for bundling and cutting. This sample preparation method is inefficient. Moreover, this method cannot be directly used to prepare thermal conductivity samples of fibers after intermittent graphitization. This is because the whole-axis fiber will be re-oriented according to the stress conditions during the intermittent graphitization process, and the treated fiber is no longer flexible. Therefore, it is necessary to ensure that the asphalt-based carbon fiber is in a straight state in the intermittent graphite furnace to ensure that the final prepared thermal conductivity sample can truly reflect the thermal conductivity of the fiber and provide reliable data support for subsequent scientific research or production applications. Summary of the invention
[0005] In view of the problem in the prior art that intermittently graphitized asphalt-based carbon fibers cannot maintain a straight state during thermal conductivity tests in the fiber direction, which affects the test accuracy, the present invention provides a method for preparing a thermal conductive sample of intermittently graphitized asphalt-based carbon fibers and a sample.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a thermally conductive sample of an intermittently graphitized asphalt-based carbon fiber comprises the following steps: S1, winding different raw material fibers according to the composition of the asphalt-based carbon fiber to be tested, to obtain an initial asphalt-based carbon fiber sample to be tested; S2, cutting and bundling the rolled asphalt-based carbon fibers, then wrapping them with graphite paper after removing the fiber heads and broken fibers, and then bundling them with PAN-based carbon fibers, marking the samples, and obtaining multiple bundles of fiber samples to be processed; S3, subjecting the fiber sample to be treated to intermittent graphitization treatment, and then folding and cutting it symmetrically along the center position, and then trimming it to obtain a short fiber sample; S5, use polyimide tape to wrap the short fiber sample in a spiral longitudinal direction to tighten it into a cylinder, and then cut it vertically along the radial direction of the cylinder to obtain a small cylindrical sample of qualified size; S6, polish the small cylindrical sample to obtain the asphalt-based graphite fiber thermal conductive sample.
[0007] Preferably, in 1, the raw materials of the asphalt-based carbon fiber sample to be tested include one or more of asphalt-based high carbon fiber treated with intermittent graphite, asphalt-based low carbon fiber treated with intermittent graphite, and asphalt-based carbon fiber treated with continuous graphitization.
[0008] Preferably, in S1, the winding tooling used during winding includes multiple unwinding shafts, wire guide rollers, a fiber winding frame and a driving machine. The multiple unwinding shafts are vertically parallel and spaced apart, and different raw material fibers are rotatably sleeved on the unwinding shafts respectively. The fiber heads are connected to the fiber winding frame through two wire guide rollers in turn; the driving machine is used to drive the fiber winding frame to rotate, and the output end of the driving machine is connected to the fiber winding frame.
[0009] Preferably, in S1, the speed of the unwinding shaft during unwinding is 1 m / min to 5 m / min.
[0010] Preferably, in S1, the initial length of the asphalt-based carbon fiber sample to be tested is 35-45 m.
[0011] Preferably, in S2, the length of each bundle of fiber samples to be processed is 20-40 cm, and the weight of each bundle is 9-12 g.
[0012] Preferably, in S3, the process conditions of the intermittent graphitization treatment are: argon atmosphere, argon flow rate of 25 L / min to 50 L / min, temperature of 2500 to 3000° C., and time of 60 min to 120 min.
[0013] Preferably, in S3, the length of the short fiber sample is 10±1 cm and the mass is 9~12 g.
[0014] Preferably, in S6, the thickness of the asphalt-based graphite fiber thermal conductive sample is 6-7 mm and the mass is 1.8-2.2 g.
[0015] A sample obtained according to the method for preparing a thermally conductive sample of an asphalt-based carbon fiber subjected to intermittent graphitization.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a thermal conductive sample of an intermittently graphitized asphalt-based carbon fiber. The asphalt-based carbon fiber is subjected to sample processing before intermittent graphitization, including processes such as unwinding, winding and cutting. After the graphitization treatment, corresponding fiber bundle bundling and cutting processes are performed to prepare the thermal conductive sample of the fiber, thereby ensuring that the asphalt-based carbon fiber remains smooth after the graphitization treatment, and at the same time improving the preparation efficiency of the thermal conductive sample of the fiber. The present invention not only provides a new idea for sample preparation, but also can realize the thermal conductive performance test of mixed fibers of different proportions, and ensures that the asphalt-based fiber remains smooth after the intermittent graphitization high-temperature treatment, without causing fiber damage. The problem of preparing thermal conductive samples of asphalt-based carbon fibers after intermittent graphitization due to reasons such as small sample quantity is solved.
[0017] Furthermore, the preparation efficiency of thermal conductive samples was improved by designing an unwinding-winding tool. At the same time, the tool can be used for the preparation of thermal conductive samples of continuous graphitized asphalt-based carbon fibers, avoiding the time-consuming and laborious problems of sample preparation and greatly improving work efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a flow chart of the method for preparing a thermal conductive sample of an asphalt-based carbon fiber subjected to intermittent graphitization of the present invention; Figure 2 It is a winding tool in a method for preparing a thermally conductive sample of an asphalt-based carbon fiber that has been intermittently graphitized according to the present invention; Figure 3 It is a structural schematic diagram of the fiber winding frame in the present invention; Figure 4 It is a schematic diagram of the fixing bracket in the present invention.
[0019] In the figure, 1, the first unwinding shaft; 2, the second unwinding shaft; 3, the third unwinding shaft; 4, the first guide roller; 5, the second guide roller. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0021] The present invention discloses a method for preparing a thermally conductive sample of an asphalt-based carbon fiber after intermittent graphitization, referring to Figure 1 , including the following steps: S1, winding different raw material fibers according to the composition of the asphalt-based carbon fiber to be tested, to obtain an initial asphalt-based carbon fiber sample to be tested; The raw materials of the asphalt-based carbon fiber samples to be tested include one or more of asphalt-based high carbon fibers treated with intermittent graphite, asphalt-based low carbon fibers treated with intermittent graphite, and asphalt-based carbon fibers treated with continuous graphitization. In this step, the selected raw material fibers are wound in a predetermined arrangement (such as parallel arrangement, cross winding, etc.) to form the initial asphalt-based carbon fiber samples to be tested. This step needs to ensure that the fibers are tightly and evenly combined to avoid gaps or looseness.
[0022] Reference Figure 2 , 3 The winding tooling used during winding includes multiple unwinding shafts, wire guide rollers, fiber winding frames and drive machines. Multiple unwinding shafts are arranged vertically in parallel and at intervals. The number of unwinding shafts is selected according to the composition of the asphalt-based carbon fiber to be tested. Different raw material fibers are rotated and sleeved on the unwinding shafts respectively. The fiber heads are connected to the fiber winding frame through two wire guide rollers in turn according to the unwinding direction and the fiber position; the drive machine is used to drive the fiber winding frame to rotate, and the output end of the drive machine is connected to the fiber winding frame. The fiber winding frame is 30cm to 40 cm long and 10cm to 20cm wide. Click the system start button, and the unwinding shaft unwinds at a speed of 1m / min to 5m / min. Pay attention to the winding position of the fiber at the winding fiber winding frame. It can be in the middle position of the fiber winding frame. Stop winding after winding 35m to 45m of carbon fiber in total. If it is continuous asphalt-based graphite fiber, it can also be used. Figure 3 , 4 In the tooling form, remove the fiber winding frame and rotate it to install it on the fixed bracket (such as Figure 4 ), since asphalt-based graphite fibers are brittle and easy to break, sampling can be carried out by manual winding, and the sampling amount is the same as described above.
[0023] S2, cut and bundle the rolled asphalt-based carbon fiber, then wrap it with graphite paper after removing the fiber heads and broken fibers, and then bundle it with PAN-based carbon fiber, and mark the samples to obtain multiple bundles of fiber samples to be processed. Carefully check each bundle of fibers to remove fiber heads, broken fibers, and other defects that may affect the test results. Twice tightening (graphite paper wrapping and PAN-based carbon fiber bundling) ensures the firmness and stability of the asphalt-based carbon fiber wrapping.
[0024] Specifically, the wound asphalt-based carbon fiber is cut at the opening, and the length of a bundle of fibers is 20 cm to 40 cm, and the weighing weight is 9 g to 12 g.
[0025] S3, the fiber sample to be treated is intermittently graphitized to further improve the thermal conductivity of the asphalt-based carbon fiber, and then folded and cut symmetrically along the center position, and then trimmed to obtain a short fiber sample with a length of 10±1cm and a mass of 9~12g.
[0026] The process conditions of intermittent graphitization treatment are: argon atmosphere, argon flow rate of 25 L / min to 50 L / min, temperature of 2500 to 3000°C, and time of 60 min to 120 min.
[0027] S5, use polyimide tape to wrap the short fiber sample longitudinally and spirally to tighten it into a cylinder, and then cut it vertically along the radial direction of the cylinder to obtain a small cylindrical sample with a thickness of 7mm to 8mm.
[0028] S6, polish the small cylindrical sample to obtain the asphalt-based graphite fiber thermal conductive sample. The specific polishing process is: first use 150#~200# sandpaper to polish the upper and lower surfaces of the cylinder, and use 1800#~2400# sandpaper to polish again to make its cross section smooth, and finally obtain the asphalt-based graphite fiber thermal conductive sample with a thickness of 6mm~7mm and a mass of 1.8g~2.2g.
[0029] The present invention also discloses a sample obtained according to the method for preparing a thermal conductive sample of asphalt-based carbon fiber after intermittent graphitization. The prepared asphalt graphite carbon fiber sample is put into a laser thermal conductivity meter (transient method) to test the thermal diffusion coefficient, and then the sample is used to test the thermal diffusion coefficient of the asphalt-based graphite carbon fiber and the fiber density, and the thermal conductivity of the asphalt-based graphite fiber is calculated based on the thermal diffusion coefficient, specific heat capacity and density data of the fiber.
[0030] The invention discloses a method for preparing a thermal conductive sample of an asphalt-based carbon fiber after intermittent graphitization. The asphalt-based carbon fiber is wound and arranged. The asphalt-based carbon fiber can be divided into asphalt-based low carbon fiber, asphalt-based high carbon fiber and asphalt-based carbon fiber high modulus fiber. Different asphalt-based carbon fibers can be wound and wound according to proportion. The wound fibers are separated, wrapped with carbon paper, and tied with PAN-based carbon fiber and put into a graphite can. The graphite can containing the asphalt-based carbon fiber is put into an intermittent graphite furnace for graphitization treatment. After the intermittent graphite furnace is cooled, the fibers are taken out, and after cutting and arranging, fiber bundling, cutting and polishing processes, an asphalt-based carbon fiber thermal conductive sample is obtained. The invention performs two sample treatments on the asphalt-based carbon fiber with intermittent graphitization treatment as the boundary, that is, unwinding, winding and cutting processes are performed before the intermittent graphitization treatment, and the corresponding fiber bundle bundling and cutting processes are performed after the intermittent graphitization treatment to prepare the fiber thermal conductive sample, thereby ensuring that the asphalt-based carbon fiber remains smooth after the graphitization treatment, and at the same time improving the preparation efficiency of the fiber thermal conductive sample.
[0031] Example 1 1) Fiber winding: Place three rolls of 2K asphalt-based high carbon fiber on the first unwinding shaft, the second unwinding shaft, and the third unwinding shaft. Figure 1The wire is moved as shown in the figure, and the fiber head is fixed at the fiber winding frame. The size of the fiber winding frame is 30cm×10cm. Click the system start button, and each unwinding shaft unwinds at an unwinding speed of 2m / min, and the fiber is wound in the middle of the fiber winding frame. After winding 20m of carbon fiber in total, the winding stops.
[0032] 2) Fiber cutting and finishing: Cut the wound asphalt-based carbon fiber at the opening. The length of a bundle of fibers is 20 cm and the weight is 9.25 g. Remove the excess fiber heads and broken fibers from each bundle of fibers, place them on graphite paper, wrap the fiber bundle with graphite paper, and bundle it with PAN-based carbon fiber. Mark the sample number on the graphite paper.
[0033] 4) Fiber loading and graphitization treatment: The bundled fiber samples were placed in a graphite tank and then placed in an intermittent graphite furnace for intermittent graphitization treatment. The treatment atmosphere was argon, the graphitization temperature was 2600°C, the treatment time was 60 min, and the argon flow rate was 30 L / min.
[0034] 5) Thermal Conductive Sample Winding and Cutting: Take out the intermittent graphitized fiber, fold the fiber symmetrically along the middle position, so that the fiber length is about 10cm, and then use scissors to cut and trim the folded fiber into 8.5cm short fibers, integrate them into a bundle with a mass of 9g, and use polyimide tape to wrap the short fibers longitudinally and spirally to tighten them into a cylinder with a diameter of 12.7mm. Then use a knife to cut vertically along the radial direction of the cylinder to obtain a small cylindrical sample with a thickness of 7.2mm.
[0035] 6) Thermal conductivity sample polishing: Use 150# sandpaper to polish the upper and lower surfaces of the cylinder, and use 2000# sandpaper to polish again to make its cross section smooth, and finally obtain a cylindrical thermal conductivity test sample with a thickness of 6mm and a diameter of 12.7mm, and a mass of 1.9g of asphalt-based graphite fiber thermal conductivity sample.
[0036] 7) Thermal conductivity test and thermal conductivity calculation: The prepared asphalt graphite carbon fiber sample was placed in a laser thermal conductivity meter (transient method) to test the thermal diffusion coefficient of 381.140 mm 2 / s, and then the sample was used to test the specific heat capacity of the asphalt-based graphite carbon fiber to be 0.709 J / (g·K) and the fiber density to be 2.150 g / cm 3 According to the thermal diffusion coefficient and specific heat capacity data of the fiber, the thermal conductivity of asphalt-based graphite fiber is calculated to be 580.990 W / (m·K).
[0037] Embodiment 2: 1) Fiber winding: Place a 2K asphalt-based high carbon fiber on the first unwinding shaft, and place a roll of 2K asphalt-based high modulus fiber on the second and third unwinding shafts respectively. The ratio of the fiber bundle is high carbon fiber: high modulus fiber = 1:2 for thermal conductive sample preparation. Figure 1 The wire is moved as shown in the figure, and the fiber head is fixed at the fiber winding frame. The fiber winding frame has a size of 30cm×20cm. Click the system start button, unwind at a speed of 1m / min, and wind the fiber in the middle of the fiber winding frame. After winding 20m of carbon fiber, stop winding.
[0038] 2) Fiber cutting: Cut the wound asphalt-based carbon fiber at the opening. The length of a bundle of fibers is 40 cm and the weight is 10.6 g. Remove the excess fiber heads and broken fibers from each bundle of fibers, place them on graphite paper, wrap the fiber bundle with graphite paper, and bundle it with PAN-based carbon fiber. Mark the sample number on the graphite paper.
[0039] 3) Fiber loading and graphitization treatment: The bundled fiber samples were placed in a graphite tank and then placed in an intermittent graphite furnace for intermittent graphitization treatment. The treatment atmosphere was argon, the graphitization temperature was 2800 °C, the treatment time was 90 min, and the argon flow rate was 25 L / min.
[0040] 4) Thermal Conductive Sample Winding and Cutting: Take out the intermittent graphitized fiber, fold the fiber twice symmetrically along the middle position to make the fiber length about 10 cm, and then cut and trim the folded fiber into 8.5 cm short fibers with scissors, integrate them into a bundle with a mass of 10.5 g, and use polyimide tape to wrap the short fibers longitudinally and spirally to tighten them into a cylinder with a diameter of 12.7 mm. Then use a knife to cut vertically along the radial direction of the cylinder to obtain a small cylindrical sample with a thickness of 6.5 mm.
[0041] 5) Thermal conductivity sample polishing: Use 200# sandpaper to polish the upper and lower surfaces of the cylinder, and use 2000# sandpaper to polish again to make its cross section smooth, and finally obtain a cylindrical thermal conductivity test sample with a thickness of 6mm and a diameter of 12.7mm, and a mass of 2.1g of asphalt-based graphite fiber thermal conductivity sample.
[0042] 6) Thermal conductivity test and thermal conductivity calculation: The prepared asphalt graphite carbon fiber sample was placed in a laser thermal conductivity meter (transient method) to test the thermal diffusion coefficient of 407.047 mm 2 / s, and then the sample was used to test the specific heat capacity of the asphalt-based graphite carbon fiber to be 0.710 J / (g·K) and the fiber density to be 2.160 g / cm 3 According to the thermal diffusion coefficient and specific heat capacity data of the fiber, the thermal conductivity of asphalt-based graphite fiber is calculated to be 624.247 W / (m·K).
[0043] Comparative Example 1: 1) Fiber winding: Continuous asphalt-based graphite fibers are used Figure 3 The tooling form in Figure 2 Remove the fiber winding frame from the Figure 4 ), sampling was carried out by manual winding, the sample was 1K graphite fiber, the size of the fiber winding frame was 35cm×10cm, the winding speed was controlled not to be too fast to prevent the graphite fiber from breaking, and the fiber winding position was in the middle of the fiber winding frame. The winding was stopped after a total of 25m of carbon fiber was wound.
[0044] 2) Fiber cutting: Cut the wound asphalt-based carbon fiber at the opening. The length of a bundle of fibers is 20 cm and the weighing weight is within 11.5 g.
[0045] 3) Thermal conductive sample winding: The fibers were symmetrically folded along the middle position to make the fiber length about 10 cm. The folded fibers were then cut and trimmed into 8.5 cm short fibers with scissors and integrated into a bundle with a mass of 11 g. Polyimide tape was used to wrap the short fibers longitudinally and spirally to tighten them into a cylinder with a diameter of 12.7 mm.
[0046] 4) Thermal conductive sample cutting: Use a knife to cut vertically along the radial direction of the cylinder to obtain a small cylindrical sample with a thickness of 7 mm.
[0047] 5) Polishing of thermal conductive samples: Use 150# sandpaper to polish the upper and lower surfaces of the cylinder, and use 2400# sandpaper to polish again to make its cross section smooth, and finally obtain a cylindrical thermal conductive test sample with a thickness of 6.5mm and a diameter of 12.7mm, and a mass of 2.0g of asphalt-based graphite fiber thermal conductive sample.
[0048] 6) Thermal conductivity test and thermal conductivity calculation: The prepared asphalt graphite carbon fiber sample was placed in a laser thermal conductivity meter (transient method) to test the thermal diffusion coefficient of 405.032 mm 2 / s, and then the sample was used to test the specific heat capacity of the asphalt-based graphite carbon fiber to be 0.710 J / (g·K) and the fiber density to be 2.150 g / cm 3 According to the thermal diffusion coefficient and specific heat capacity data of the fiber, the thermal conductivity of asphalt-based graphite fiber is calculated to be 618.281 W / (m·K).
[0049] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.
Claims
1. A method for preparing a thermally conductive sample of an asphalt-based carbon fiber after intermittent graphitization, characterized in that: The following steps are involved: S1, winding different raw material fibers according to the composition of the asphalt-based carbon fiber to be tested, to obtain an initial asphalt-based carbon fiber sample to be tested; S2, cutting and bundling the rolled asphalt-based carbon fibers, then wrapping them with graphite paper after removing the fiber heads and broken fibers, and then bundling them with PAN-based carbon fibers, marking the samples, and obtaining multiple bundles of fiber samples to be processed; S3, subjecting the fiber sample to be treated to intermittent graphitization treatment, and then folding and cutting it symmetrically along the center position of the length, and then trimming it to obtain a short fiber sample; S5, use polyimide tape to wrap the short fiber sample in a spiral longitudinal direction to tighten it into a cylinder, and then cut it vertically along the radial direction of the cylinder to obtain a small cylindrical sample of qualified size; S6, polish the small cylindrical sample to obtain the asphalt-based graphite fiber thermal conductive sample.
2. The method for preparing a thermally conductive sample of an intermittently graphitized pitch-based carbon fiber according to claim 1, characterized in that: In S1, the raw materials of the asphalt-based carbon fiber sample to be tested include one or more of asphalt-based high carbon fiber treated with intermittent graphite, asphalt-based low carbon fiber treated with intermittent graphite, and asphalt-based carbon fiber treated with continuous graphitization.
3. The method for preparing a thermally conductive sample of an intermittently graphitized pitch-based carbon fiber according to claim 1, characterized in that: In S1, the winding tooling used during winding includes multiple unwinding shafts, wire guide rollers, a fiber winding frame and a driving machine. The multiple unwinding shafts are arranged in parallel and spaced apart vertically, and different raw material fibers are rotatably sleeved on the unwinding shafts respectively. The fiber heads are connected to the fiber winding frame through two wire guide rollers in turn; the driving machine is used to drive the fiber winding frame to rotate, and the output end of the driving machine is connected to the fiber winding frame.
4. The method for preparing a thermally conductive sample of an intermittently graphitized pitch-based carbon fiber according to claim 3, characterized in that: In S1, the speed of the unwinding shaft during unwinding is 1 m / min to 5 m / min.
5. The method for preparing a thermally conductive sample of an intermittently graphitized pitch-based carbon fiber according to claim 1, characterized in that: In S1, the initial length of the asphalt-based carbon fiber sample to be tested is 35~45m.
6. The method for preparing a thermally conductive sample of an intermittently graphitized pitch-based carbon fiber according to claim 1, characterized in that: In S2, the length of each bundle of fiber samples to be processed is 20-40 cm, and the weight of each bundle is 9-12 g.
7. The method for preparing a thermally conductive sample of an intermittently graphitized pitch-based carbon fiber according to claim 1, characterized in that: In S3, the process conditions of the intermittent graphitization treatment are: argon atmosphere, argon flow rate of 25 L / min to 50 L / min, temperature of 2500 to 3000° C., and time of 60 min to 120 min.
8. The method for preparing a thermally conductive sample of an intermittently graphitized pitch-based carbon fiber according to claim 1, characterized in that: In S3, the length of the short fiber sample is 10 ± 1 cm and the mass is 9~12 g.
9. The method for preparing a thermally conductive sample of an intermittently graphitized pitch-based carbon fiber according to claim 1, characterized in that: In S6, the thickness of the asphalt-based graphite fiber thermal conductive sample is 6~7mm and the mass is 1.8~2.2g.
10. A sample obtained by the method for preparing a thermal conductive sample of a pitch-based carbon fiber through intermittent graphitization according to any one of claims 1 to 9.